Four new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Afrotropical Region - Wang, Xiu-Dan; Dietrich, Christopher H.; Zhang, Ya-Lin (Zootaxa, 2018)
Three new species from Republic of the Congo, Brasura sinistra, B. piscinura and Tialidia hama spp. nov., and one new species Limentinus declinatus sp. nov. from Madagascar are described and illustrated in this paper.